Colour Ball Based on Microcontroller as A Educational Games Tools for Early Chilhood Learning - Ihtiari Prastyaningrum; Umi Kholifah; Dian Ratnaningtyas Afifah; Sofia Nur Afifah (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The use of technology for educational game tools or known as APE in early childhood still needs to be developed. This research aims to develop technology-based educational game tools for early childhood learning. Apart from that, it also aims to ensure that children understand earlier about using technology wisely and purposefully. APE Color Ball is designed in such a way that children will be able to get many benefits from one activity. This type of research is development research. The subjects involved as samples were teachers and students. This research chose the ADDIE (Analysis, Design, Development, Implementation, Evaluation) method to achieve the targeted objectives. The instruments used in this research were validation sheets, questionnaires and observation sheets. Through research activities and data analysis, it was found that Color Ball is suitable for use as a learning medium, in this case it functions as an APE for Kindergarten Class A. Based on observations with teachers and students of Kindergarten Class A, in One time learning activity using Color Ball students can get three benefits at once, namely motor activity, color recognition and introduction to simple English vocabulary. This benefit is very important to support children's development, especially in the current era of technological advances.